SOCIAL STRUGGLE IN DAGESTAN VILLAGE IN THE SECOND HALF OF THE XIX CENTURY - Dalgat, E M (History, Archeology and Ethnography of the Caucasus, 2016)
The author of the article analises the social struggle in the Dagestan village in the post-reform period, the causes of this struggle, the driving forces and the form in which it occurred, and the value of it.